Penggunaan Media Audio Visual dalam Mengembangkan Pengetahuan dan Keterampilan Sholat Anak - Yusria; Ridwan; Latifah Nuraini (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study addresses the limited understanding of prayer (shalat) procedures among early childhood students, which often results in difficulties in memorizing the correct sequence of movements and recitations, thereby affecting the overall quality of worship at both school and home. The primary objective is to analyze the effectiveness of audio-visual media in improving children’s cognitive and psychomotor competencies related to prayer. Employing a qualitative approach within the framework of Classroom Action Research (CAR), the study was conducted in two cycles involving 20 children from group B-B at RA Al-Jauharen, Kota Jambi, during the 2024/2025 academic year. Data were collected through observation, interviews, and documentation, and analyzed descriptively to identify changes in students’ learning behavior and performance. The results demonstrate that the use of audio-visual media significantly enhanced students’ engagement, facilitated comprehension of prayer sequences and recitations, and improved accuracy and fluency in practice sessions. Additionally, children exhibited higher levels of confidence and active participation during instructional activities. These findings highlight the pedagogical potential of integrating audio-visual media as an innovative and effective strategy in early childhood Islamic education, particularly for teaching prayer in a more interactive and memorable manner.